Some comparative aspects of corporate rescue in South African company law - Loubser, Anneli (University of South Africa, 2010)
South African company law has provided for the rescue of financially distressed companies since 1926 when the statutory procedure of judicial management was introduced by the Companies Act 46 of 1926. Unfortunately, judicial management has never been regarded as a successful corporate rescue procedure and for most of its existence it has been severely criticised on many grounds. The Companies Act 61 of 1973 that replaced the Companies Act 46 of 1926 did very little to improve this situation and judicial management remained underutilised. As a result, the Companies Act 71 of 2008 now introduces two newly-created corporate rescue procedures in the form of business rescue proceedings and the compromise with creditors. This study analyses judicial management and the new corporate rescue procedures to establish whether the identified weaknesses of judicial management have been adequately and effectively addressed in the new procedures. A comparative study with similar procedures in England and Germany is undertaken to determine whether the South African legislature has delivered on its promise to create a system of corporate rescue that will meet the needs of a modern South African economy. Several weaknesses in the new procedures are identified and a number of recommendations are made to improve the relevant provisions and to assist in providing South African company law with an efficient and acceptable corporate rescue regime.
https://uir.unisa.ac.za/handle/10500/3575
Keywords: Bankruptcy; Business failures; Business recovery; Business rescue; Corporate insolvency; Corporate reorganizations; Corporate rescue; Corporation law; Debtor and creditor; Financial distress; Insolvency; Insolvency practitioners